2,4-Dichlorophenoxyacetic Acid in the Gas and Crystal Phases and Its Intercalation in Montmorillonite—An Experimental and Theoretical Study - Claro Ignacio Sainz-Díaz; Nelly L. Jorge; Jorge M. Romero; André Grand; Alfonso Hernández-Laguna (Molecules)
Many properties of 2,4-dichlorophenoxyacetic acid (2,4-D) depend on its molecular environment, such as whether it is an isolated molecule, a dimer, or in a crystalline state. The molecular geometry, conformational analysis, and vibrational spectrum of 2,4-D were theoretically calculated using Density Functional Theory (DFT) methods. A new slightly more stable conformer was found, which is different to those previously reported. The most stable conformer shows a dimer by means of hydrogen bonds between the carboxylic groups of both molecules, which agrees with the experimental results. The crystal structure of 2,4-D was also calculated with 3D periodical boundary conditions at the DFT level. From the theoretical IR spectra, a vibrational analysis of this molecular species was accomplished, and the bands were reassigned. 1H and 13C NMR in the dissolution and solid states, respectively, showed intramolecular hydrogen bonds between carboxylic acid groups. The dimer is more stable than the isolated molecule. All these results indicated that the dimer can also exist in the solid state, which could explain the low solubility of this compound. In addition, the intercalation of 2,4-D into the confined interlayer space of montmorillonite was also calculated, and it was found that the adsorption is energetically favourable. This result was experimentally confirmed. These findings predicted that these natural clay minerals, which are found in the environment, can be excellent adsorbents for the 2,4-D pollutant.